2018
DOI: 10.1186/s13002-018-0249-0
|View full text |Cite
|
Sign up to set email alerts
|

Local botanical knowledge of native food plants in the semiarid region of Brazil

Abstract: BackgroundThis study aimed to investigate the local botanical knowledge of native food plants in three rural communities, located in the semiarid region of Paraíba State, Brazil, verifying possibilities of differences of knowledge among communities and between men and women.MethodsSemi-structured interviews about native plant knowledge and use were conducted with all householders in each community, totaling 117 informants. The species similarity among the communities of Pau D’Arco, Várzea Alegre, and Barroquin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 31 publications
(31 reference statements)
1
18
0
8
Order By: Relevance
“…Species listed as having potential use value (UV p ) are also potential targets for effective use since well-known species are those that are most used, and in the absence or extinction of species actually used, species with potential use value can be incorporated into effective usage in the future (Lucena et al 2012). In this way, the results demonstrate that the application of use values based on differentiated formulas provides more cohesive and in-depth diagnoses regarding the cultural importance of the mentioned species and contributes to conservation studies and initiatives (Lucena et al 2012;Ribeiro et al 2014;Nunes et al 2018;Soares et al 2018a, b;Santos et al 2019).…”
Section: Discussionmentioning
confidence: 79%
“…Species listed as having potential use value (UV p ) are also potential targets for effective use since well-known species are those that are most used, and in the absence or extinction of species actually used, species with potential use value can be incorporated into effective usage in the future (Lucena et al 2012). In this way, the results demonstrate that the application of use values based on differentiated formulas provides more cohesive and in-depth diagnoses regarding the cultural importance of the mentioned species and contributes to conservation studies and initiatives (Lucena et al 2012;Ribeiro et al 2014;Nunes et al 2018;Soares et al 2018a, b;Santos et al 2019).…”
Section: Discussionmentioning
confidence: 79%
“…The results presented here show the importance of adopting the UV current in the analysis of ethnobiological data since this UV explains the effective use of natural resources and is significantly different from the UV general of the species, based on the Cluster test and one-wayANOVA. No studies had statistically measured this difference, until now, although some authors have pointed out the need to assess the applicability of this index [92, 107, 113115]. Therefore, the data from this research suggest a new standard for data analysis using the UV current as a strategic tool for the conservation of the most important species.…”
Section: Discussionmentioning
confidence: 92%
“…Some studies [90, 107, 113115] have shown that the application of differentiated UV results in more precise diagnoses regarding the cultural importance of the species used. Thereby, aiming at strategies for the conservation of these animals, further studies are needed to evaluate if the local decrease in the population of some species, from the informants’ point of view, is directly related to their use and/or to other factors, such as population fluctuation and changes in their habitat, among others.…”
Section: Discussionmentioning
confidence: 99%
“…However, it does not distinguish between current use (effective) and potential use; therefore, the application of the UV g becomes unreliable for allocating a high number of potential uses in the analysis. This distinction between knowledge and effective use needs to be addressed in future studies for the development of conservation and management initiatives based on accurate information, for species that are actually under pressure [ 20 , 34 , 35 , 44 ].…”
Section: Resultsmentioning
confidence: 99%